(untitled) (Annals of Medical Research, 2021)
Aim: Along with the increased availability of radiologic imaging methods, early identification of tumor tissue, and patient surveillance programs; ductal carcinoma in situ (DCIS) and microinvasive DCIS became more commonly identified in the tru-cut biopsy specimens and resected samples of patients. Pathological examinations of the excision materials from these patients reveal invasive tumors, microinvasions or DCIS alone. Recently, it has become debatable whether to perform a sentinel lymph node biopsy (SLNB) in patients diagnosed with DCIS or microinvasive DCIS. In this present study, we evaluated the diagnosis made by examining the excision material, any presence of lymph node metastases, and the relationship of hormone profile to the presence of metastases in the patients diagnosed with DCIS or microinvasive DCIS by the examination of tru-cut biopsy specimens. Based on our study results, we discussed the requirement for SLNB in patients with a tru-cut diagnosis of DCIS or microinvasive DCIS. Materials and Methods: The study included 172 patients, who underwent surgical excision and SLNB after receiving a tru-cut biopsy diagnosis of DCIS and microinvasive DCIS in our hospital from the year 2010 to 2018. Results: Tru-cut biopsy diagnoses were DCIS and microinvasive DCIS in 69.8% (120 patients) and 30.2% (52 patients) respectively. SLNB metastases were identified in 35.8% (n=43) of the DCIS positive patients and 44.2% (n=23) in the microinvasive DCIS positive patients. The diagnosis of invasive ductal carcinoma after mastectomy was made at a rate of 90.0% (n=108) among the DCIS positive patients and 92.3% (n=48) among the microinvasive DCIS positive patients. Conclusion: SLNB metastases were found in 35.8% (n=43) and 44.2% (n=23) of the DCIS positive patients and microinvasive DCIS positive patients, respectively. We conclude that SLNB should be favorably proper to perform in the patients with tru-cut diagnoses of DCIS and microinvasive DCIS because a high rate of SLNB metastases was detected in our DCIS and microinvasive DCIS patients and a high rate of invasive ductal carcinoma diagnosis was made after examining the excision material of these patients.